1998
DOI: 10.1161/01.cir.98.19.2000
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Inflammatory Cells in Atherosclerotic Plaques Relates to the Direction of Flow

Abstract: Significant differences in cell composition between upstream and downstream parts of plaques indicate a role for arterial flow in the distribution of different cell types. The low-flow/low-shear downstream areas of plaques contain significantly more SMCs, which could provide the background for slowly progressive growth at distal ends of plaques. The significantly high number of macrophages in the upstream areas suggests a relationship between high flow/high shear and plaque instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
104
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 29 publications
14
104
2
5
Order By: Relevance
“…In vivo post-mortem studies have revealed that plaque disruption usually occurs at the shoulders (6,(25)(26)(27), where the cap is often thinnest and most heavily infiltrated with white blood cells including neutrophils and monocytes (28). Inflammatory markers are also differentially expressed in vivo in disturbed flow regions, such as those created by an eccentric stenosis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo post-mortem studies have revealed that plaque disruption usually occurs at the shoulders (6,(25)(26)(27), where the cap is often thinnest and most heavily infiltrated with white blood cells including neutrophils and monocytes (28). Inflammatory markers are also differentially expressed in vivo in disturbed flow regions, such as those created by an eccentric stenosis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…15,43 Because vascular cell adhesion molecule-1 expression is correlated with and can contribute to the entry of macrophages into the intima, 44 its downregulation by probucol could attenuate atherosclerosis by decreasing the intimal accumulation of macrophages. 38 The expression of adhesion molecules 44 and the distribution of inflammatory cells within the vessel wall 45 are affected by arterial blood flow, so that these local differences in hemodynamic factors could be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…24) The elevated systolic forces from cardiac hypertrophy, 25) shear stress, and increase in circumferential wall tension 26,27) in hypertensive patients may take part in the worsening of the plaque progression and disruption.…”
Section: Discussionmentioning
confidence: 99%